A Novel Variant in ABCD1 Gene Presenting as Adolescent-Onset Atypical Adrenomyeloneuropathy With Spastic Ataxia - Chen, Yanxing; Zhang, Jianfang; Wang, Jianwen; Wang, Kang (Frontiers in Neurology, 2018)
X-linked adrenoleukodystrophy (X-ALD) is a rare neurological disorder with a highly complex clinical presentation. Adrenal function, spinal cord, peripheral nerves, and cerebral white matter are commonly affected in adult-onset male patients. Here, we report a family with unusual presentation of X-ALD. The 19-year-old proband had presented with atypical symptoms of adrenomyeloneuropathy (AMN) for 3 years, only with spastic paraparesis, cerebellar ataxia, and cerebellar atrophy with white matter hyperintensity. It is rare for an AMN male patient to present the initial symptoms at such an early age with the adrenal function, sphincter function, and dorsal column of the spinal cord spared. He is also the youngest male AMN patient reported to have cerebellar ataxia. His mother also presented unusually early onset of the similar manifestations. A novel variant c.1144A>C (p.Thr382Pro) in exon3 of the ABCD1 gene was identified. Family study involving the grandparents of the proband revealed the de novo occurrence of the variant in the mother.